Changes in inorganic and organic matters in processed water from hydrothermal-treated biogas slurry - Xiaofei Ge; Tao Zhang (Materials Science for Energy Technologies, 2023)
Carbon neutrality innovation technologies are a leading research topic in sustainable development. Among these, anaerobic digestion is considered as a better choice for biowaste utilization. However, large amounts of produced biogas slurry hamper the widespread application of anaerobic digestion. The hydrothermal process is regarded as favorable to treat biogas slurry. The effects of inorganic and organic matter in processed water from the hydrothermal-treated biogas slurry were investigated in our research. The changes in inorganic elements such as P, Ca, Mg, Cu, and Zn were detected at different reaction temperatures (90, 120, 150, 180, 210, and 240 ℃) and acid catalytic conditions (0.5, 1, 2, 3, 4, 4.5, and 5 mL 5 M HCl). The changes in organic matter were analyzed using three-dimensional excitation emission matrix fluorescence spectroscopy. With the increase in the hydrothermal reaction temperatures, the quantity of total and inorganic P and the concentration of Ca initially increased and then decreased, concentration of Mg remained constant, while the concentration of Zn and Cu showed a trend of initial decrease and then increase, and the macromolecular organic matter was hydrolyzed into small, soluble molecular organic matter. With the increase in HCl, the amount of released total and inorganic P and concentrations of Ca, Mg, Zn, and Cu increased, and the macromolecular organic matter was hydrolyzed into small molecular organic matter. The hydroponic testing indicated that the processed water has a positive effect on the growth of maize. These results provide critical findings on the reuse of biogas slurry, which is useful for biowaste management and improves carbon neutrality strategy.